TEACHERS’ PROBLEMS IN USING INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) AND ITS IMPLICATIONS IN ELEMENTARY SCHOOLS - Ningsih, Sutria; Eko Kuntarto; Kurniawan, Agung Rimba (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is a qualitative research with a type of case study research. The purpose of this study is to find out the problems/obstacles faced by teachers in using Information and Communication Technology (ICT). Information and Communication Technology (ICT) is a tool used to convey information related to the processing, management, and transfer of information. As for the types of Information and Communication Technology (ICT) that were the focus of research include computers/laptops and LCD projectors. In this era of globalization, teachers are required to be able to use ICT in the learning process to add insight and help teachers in adding teaching material with the use of ICT in the learning process. The findings from the research results concluded that problems/obstacles that occur in the use of ICT in primary schools include time-consuming preparation, limited number of infocus, students’ lack of focus on the material, and the unavailability of facilities.